2015
DOI: 10.2147/cia.s92650
|View full text |Cite
|
Sign up to set email alerts
|

Preferred health behaviors and quality of life of the elderly people in Poland

Abstract: PurposeThe aim of this study was to assess possible differences between a group of residents of public nursing homes (PNH) and a group of members of Universities of the Third Age (UTA) measured using standard psychometric scales.Materials and methodsThe research was conducted between January 3, 2013 and February 15, 2014 on a group of 200 residents of PNH and 200 members of the UTA using five psychometric scales: Standardized Satisfaction with Life Scale (SWLS), Standardized Health Behavior Inventory (HBI), St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 17 publications
4
24
1
1
Order By: Relevance
“…Given the results, the comparative study of the QOL among the elderly is sought. The female majority in the sample is close to other findings [26][27][28]. Even given this reality in both scenarios, the gender was not significantly associated with QOL.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Given the results, the comparative study of the QOL among the elderly is sought. The female majority in the sample is close to other findings [26][27][28]. Even given this reality in both scenarios, the gender was not significantly associated with QOL.…”
Section: Discussionsupporting
confidence: 78%
“…In Poland, an investigation into family emotional support highlighted the significant difference for non-institutionalized elderly people [27]. In this study, there was asimilarity between elderly people who have and those who does not have companionship.…”
Section: Discussionmentioning
confidence: 62%
“…This finding may be related to better support of elderly people by their families in their own homes. Another study has shown that greater life satisfaction is associated with receiving more family support (33).…”
Section: Discussionmentioning
confidence: 99%
“…Not following a healthy lifestyle is a risk factor of modern civilization diseases because the health of an individual is mainly determined by their individual health behaviours [26,28]. It is estimated that the main cause of death in developing and developed countries are cardiovascular diseases [4,13].…”
Section: Discussionmentioning
confidence: 99%
“…A properly shaped, healthy way of life improves the health of the individual, and consequently, the health of the population. Lifestyle is considered to be the main factor as it determines health in over 50% [28,29,30].…”
Section: Introductionmentioning
confidence: 99%